2009
DOI: 10.1038/npp.2009.193
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cocaine-Induced H3 Acetylation and Transcriptional Activation of CaMKIIα in the Nucleus Accumbens Is Critical for Motivation for Drug Reinforcement

Abstract: The regulation of gene expression in the brain reward regions is known to contribute to the pathogenesis and persistence of drug addiction. Increasing evidence suggests that the regulation of gene transcription is mediated by epigenetic mechanisms that alter the chromatin structure at specific gene promoters. To better understand the involvement of epigenetic regulation in drug reinforcement properties, rats were subjected to cocaine self-administration paradigm. Daily histone deacetylase (HDAC) inhibitor infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 74 publications
9
156
1
Order By: Relevance
“…These findings are interesting given that dopamine D1-like agonists increase AMPAR insertion into NAC MSNs through a process involving CAMKIIa (Anderson et al, 2008;Sun et al, 2008) and that both dopamine and CAMKIIa have been shown to be important for the expression of psychostimulant sensitization and drugseeking behavior (Licata and Pierce, 2003;Loweth et al, 2008;Pierce et al, 1998). In fact, lentiviral-mediated knockdown of CAMKIIa in the NACsh reduced motivation to self-administer cocaine on a PR schedule (Wang et al, 2010a). Collectively, these data support a hypothesis in which mTORC1 acts as a key effector in the molecular pathway controlling the dynamic regulation of synaptic proteins within the NAC that are required for the expression and maintenance of drug reward.…”
Section: Intra-cerebroventricular Mtorc1 Inhibition Reduces Pr Responsupporting
confidence: 64%
“…These findings are interesting given that dopamine D1-like agonists increase AMPAR insertion into NAC MSNs through a process involving CAMKIIa (Anderson et al, 2008;Sun et al, 2008) and that both dopamine and CAMKIIa have been shown to be important for the expression of psychostimulant sensitization and drugseeking behavior (Licata and Pierce, 2003;Loweth et al, 2008;Pierce et al, 1998). In fact, lentiviral-mediated knockdown of CAMKIIa in the NACsh reduced motivation to self-administer cocaine on a PR schedule (Wang et al, 2010a). Collectively, these data support a hypothesis in which mTORC1 acts as a key effector in the molecular pathway controlling the dynamic regulation of synaptic proteins within the NAC that are required for the expression and maintenance of drug reward.…”
Section: Intra-cerebroventricular Mtorc1 Inhibition Reduces Pr Responsupporting
confidence: 64%
“…Histone acetylation plays an important role in learning and memory (Alarcon et al 2004;Vecsey et al 2007) as well as in drug addiction (Levine et al 2005(Levine et al , 2011Renthal and Nestler 2008;Wang et al 2010). Our previous work has found that the administration of the HDAC inhibitor SAHA (suberoylanilide hydroxamic acid) can simulate the priming effect of nicotine on cocaine in the expression of LTP in the NAc and amygdala (Levine et al 2011;Huang et al 2013).…”
Section: Histone Acetylation Mediates the Priming Effect In The Dgmentioning
confidence: 99%
“…In drug addiction, for example, repeated cocaine administration elevates global histone acetylation levels in reward-related brain regions, such as the nucleus accumbens (NAc) . Furthermore, manipulation of histone acetyltransferases (HATs) and histone deacetylases (HDACs) by pharmacological inhibition, viralmediated gene transfer, and/or knock-out models has confirmed that histone acetylation is critically involved in behavioral and molecular responses to cocaine (Kumar et al, 2005;Sun et al, 2008;Im et al, 2010;Malvaez et al, 2010Malvaez et al, , 2011Malvaez et al, , 2013Wang et al, 2010;Kennedy et al, 2013;. As a consequence, HAT and HDAC inhibitors have emerged as attractive targets for the treatment of drug addiction; however, additional reg-ulators of histone lysine acetylation have recently come to light.…”
Section: Introductionmentioning
confidence: 99%